Central versus peripheral mechanisms of cold-induced vasodilation: a study in the fingers and toes of people with paraplegia - Lydia Tsoutsoubi; Leonidas G. Ioannou; Billie K. Alba; Stephen S. Cheung; Hein A. Daanen; Igor B. Mekjavic; Andreas D. Flouris (European Journal of Applied Physiology, 2023)
Purpose This study examined physiological and perceptual parameters related to cold-induced vasodilation (CIVD) in the fingers and toes of people with paraplegia and compared them with responses observed in able-bodied individuals. Methods Seven participants with paraplegia and seven able-bodied individuals participated in a randomized matched-controlled study involving left-hand and -foot immersion in cold water (8 ± 1 °C) for 40 min during exposure to cool (16 ± 1 °C), thermoneutral (23 ± 1 °C), and hot (34 ± 1 °C) ambient conditions. Results Similar CIVD occurrence was observed in the fingers in the two groups. In toes, three of the seven participants with paraplegia revealed CIVDs: one in cool, two in thermoneutral, and three in hot conditions. No able-bodied participants revealed CIVDs in cool and thermoneutral conditions, while four revealed CIVDs in hot conditions. The toe CIVDs of paraplegic participants were counterintuitive in several respects: they were more frequent in cool and thermoneutral conditions (compared to the able-bodied participants), emerged in these conditions despite lower core and skin temperatures of these participants, and were evident only in cases of thoracic level lesions (instead of lesions at lower spinal levels). Conclusion Our findings demonstrated considerable inter-individual variability in CIVD responses in both the paraplegic and able-bodied groups. While we observed vasodilatory responses in the toes of participants with paraplegia that technically fulfilled the criteria for CIVD, it is unlikely that they reflect the CIVD phenomenon observed in able-bodied individuals. Taken together, our findings favor the contribution of central over peripheral factors in relation to the origin and/or control of CIVD.